2021
DOI: 10.3389/fcvm.2021.758548
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Polygraphy for Detection of Obstructive Sleep Apnea in Patients With Atrial Fibrillation

Abstract: Background: Obstructive sleep apnea (OSA) is a modifiable risk factor of atrial fibrillation (AF) but is underdiagnosed in these patients due to absence of good OSA screening pathways. Polysomnography (PSG) is the gold standard for diagnosing OSA but too resource-intensive as a screening tool. We explored whether cardiorespiratory polygraphy (PG) devices using an automated algorithm for Apnea-Hypopnea Index (AHI) determination can meet the requirements of a good screening tool in AF patients.Methods: This pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(27 reference statements)
3
6
0
Order By: Relevance
“…It is also well known that the coupling or synchronization between heartbeat and blood pressure is also regulated by respiration through neural effects on cardiac vagal activity and mechanical effects on stroke volume and intrathoracic pressure ( Mejía-Mejía et al, 2018 ). Desynchronizations between cardiorespiratory coupling and/or cardiovascular coupling were reported following hypertension, myocardial infarctions, depression, obstructive sleep apnea and acute insomnia ( Shigdel et al, 2019 ; Zhao et al, 2019 ; Delesie et al, 2021 ). In the present study, we found declined coupling strength of cardiorespiratory and respiratory-cardiovascular of healthy young subjects after 24-h ATSD.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well known that the coupling or synchronization between heartbeat and blood pressure is also regulated by respiration through neural effects on cardiac vagal activity and mechanical effects on stroke volume and intrathoracic pressure ( Mejía-Mejía et al, 2018 ). Desynchronizations between cardiorespiratory coupling and/or cardiovascular coupling were reported following hypertension, myocardial infarctions, depression, obstructive sleep apnea and acute insomnia ( Shigdel et al, 2019 ; Zhao et al, 2019 ; Delesie et al, 2021 ). In the present study, we found declined coupling strength of cardiorespiratory and respiratory-cardiovascular of healthy young subjects after 24-h ATSD.…”
Section: Discussionmentioning
confidence: 99%
“…All previous validation studies for these tools were conducted in sleep/surgical clinics or community settings. 41,[45][46][47][48][49][50][51][52][53][54][55][56] The present study demonstrated that, in cancer patients, either SBQ or ApneaLink™Air were modestly effective at excluding patients without severe OSA, with no additional benefit gained when using them in combination. However, both methods were ineffective at identifying patients with moderate-to-severe or severe OSA.…”
Section: Discussionmentioning
confidence: 50%
“…Unfortunately, despite extensive research, the mechanisms underlying AF are complex and not completely understood yet [ 1 , 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Obstructive sleep apnea (OSA) is a common chronic disorder affecting about 2–4% of the adult population, being more common in old men [ 19 ]. The condition is characterized by repetitive episodes of the complete or partial collapse of the upper airway during sleep, with a consequent cessation/reduction of the airflow [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the prevalence of OSA in patients with AF is unknown because OSA is generally underdiagnosed [ 19 , 20 ]. Furthermore, controversy over this association and its directionality exists, because of the high incidence of cardiovascular (CV) comorbidities in patients with OSA and AF.…”
Section: Introductionmentioning
confidence: 99%